Ethical Leadership and Employee Performance in the Public Sector: The Mediating Effects of Motivation and Satisfaction - Kazeem Adebayo Oladimeji; Abdulrazaq Kayode Abdulkareem (Jurnal Studi Pemerintahan)
This study examined the influence of ethical leadership on employee performance in the public sector, using employee motivation and employee satisfaction as mediators. This study is motivated by the need to examine the influence of ethical behavior of leaders in the public sectors in a developing country often marred with corruption allegations and poor public service delivery. This study is designed quantitatively, and data was collected through a structured questionnaire distributed among federal civil servants across five Ministries in Nigeria. A conceptual model was designed based on seven hypotheses and tested using PLS-SEM technique. Findings revealed that all hypotheses were significant based on p<0.001. More importantly, ethical leadership positively and significantly influence employee motivation and satisfaction. Also, employee motivation and satisfaction mediate the relationship between ethical leadership and employee performance. These findings suggest the importance of leaders’ moral behavior and their relationship with subordinates in the workplace, through motivating them to work, as well as imbibing the workplace ethics and culture. Practically, the findings imply that promoting workplace ethics becomes a crucial ingredient in stimulating individual performance, which translates to overall organizational performance and better service delivery to the citizens.